Web-Based Online Library Design to Improve Student Literacy - Baan, Anastasia; Ervianti; Putra Pratama, Muh. (Universitas Pendidikan Ganesha, 2024)
The current obstacles are that awareness of reading books is decreasing along with the development of the online world, especially in the world of education, and interest in reading is decreasing directly by visiting the library. Therefore, this study develops a virtual library as a web that can be accessed anytime and anywhere. The purpose of this study is development research that starts from needs analysis and needs identification, designing and developing a web-based online library, validity and practicality tests, and effectiveness through product implementation and evaluation trials. This stage refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) for this study to the development stage. The subjects in this study were two material experts and two media experts. The trial subjects were students of the Faculty of Teacher Training and Education. Data collection techniques used questionnaires, documentation, and interviews. This study used a data collection instrument in the form of a questionnaire. Data analysis techniques used qualitative descriptive analysis and quantitative descriptive analysis. The study's results, namely the validation of Media Experts, showed very feasible criteria. Based on user responses, the responses are in the very practical category. It was concluded that user responses strongly agreed with the use of online libraries in improving literacy. The research implies that the results can be used as a basis for developing future policies and strategies for library services. This includes determining the technology and service development focus most relevant to user needs.